(untitled) (Scientific journal of the Fergana State University, 2026)
This article focuses on the development of gender culture in students as a socio-pedagogical necessity and the support of women, the formation of the concept of gender in the process of the theoretical development of feminism, and then directly within the framework of gender studies.